A new hardness model for materials design in cemented carbides. (September 2018) - Walbrühl, Martin; Linder, David; Ågren, John; Borgenstam, Annika
Abstract: The Materials Design approach offers new possibilities towards property-oriented materials development. The performance of cemented carbides is significantly influenced by properties like the hardness and fracture toughness. Fundamentally based phenomenological models, which allow for prediction of the properties of interest, make it possible to tailor the properties of the material based on the required performance. None of the previously available models are suitable to actively design the cemented carbide hardness because they are valid only for Co binders and do not allow alternative binder phases. The hardness is greatly influenced by the chemistry, binder volume fraction and carbide grain size. Only the chemistry, specifically the binder composition, leaves the possibility to optimize the binder hardness and to exceed classical WC-Co cemented carbides. Specifically focusing on the design of the binder phase, a new binder hardness description is implemented in a modified Engqvist hardness model and allows description of a wider range of conventional and alternative systems. The model was validated for various published cemented carbide systems and is able to predict their hardness within a 10% error. The assessed systems contain classical Co binders as well as alternative, austenitic binders based on Fe, Ni and Co. Highlights: A generalized cemented carbide hardness model for various classical and alternative binder systems is presented. The model considers non-equilibrium solubilities in classical Co and alternative binder systems. The non-equilibrium solubilities are used in a solid solution strength model to predict the binder hardness.